UNDERSTANDING THE ASPECTS OF LEARNING AND LEARNERS: A CONCEPTUAL ANALYSIS - Bulqia Mas'ud (Edu Global : Jurnal Pendidikan Islam, 2020)
The main focus of this research is to understand the meaning of learning and the nature of a learner. The analysis elaborates who learners are, where learners can be found, when learners and how learning happens. Besides, the article also explicates intelligence, information processing and motivation in learning. The discussion of the article explains that learning happens in any circumstances throughout human development and generates some changes in cognition and behavior. Furthermore, the learning process begins when humans face external stimuli through human interaction. The stimuli continue to be processed in the brain to activate thinking process hence it is called cognitive development. In the next discussion, we put forward that learning requires both logical-reasoning and emotional intelligence. Logical-reasoning is related to information processing in the brain. It is a process where human mind is being active when receiving, storing, and retrieving information hence new knowledge is gained after processed in human information processing system. While, emotional Intelligence is social intelligence which connects between learners’ emotional, social, and cognitive wellbeing. In the last discussion, we suggest that the effectiveness of learning needs good motivation which is influenced by the internal encouragement of human behavior, expectancy-value theory, and goal setting.